Dysregulation of c-Jun (JUN) and FBJ murine osteosarcoma viral oncogene homolog B (FOSB) in obese people and their predictive values for metabolic syndrome - Chenxi Yang; Yi Chen; Guangfeng Tang; Tongtong Shen; Li Li (Endocrine Journal)
The incidences of metabolic syndrome (MetS), denoting insulin resistance-associated various metabolic disorders, are increasing. This study aimed to identify new biomarkers for predicting MetS and provide a novel diagnostic approach. Herein, the expression profiles of c-Jun (JUN) and FBJ murine osteosarcoma viral oncogene homolog B (FOSB) in individuals with obesity and patients with MetS from the Gene Expression Omnibus database. Quantitative reverse transcription polymerase chain reaction (RT-qPCR) was used to evaluate the messenger RNA levels of JUN and FOSB in the peripheral blood of healthy volunteers (lean and obese) and patients with MetS (lean and obese), along with that in the adipose tissue and peripheral blood of obese mouse model. Furthermore, receiver operating characteristic (ROC) curve and logistic regression analyses were performed to determine the diagnostic value of JUN and FOSB in MetS. The expression profiles and RT-qPCR results showed that JUN and FOSB were highly expressed in individuals with obesity, obese mouse models, and patients with MetS. The ROC analysis results showed an area under the curve values of 0.872 and 0.879 for JUN, 0.802 and 0.962 for FOSB, and 0.946 and 0.979 for JUN–FOSB in the lean group and the group with obesity, respectively, in predicting MetS. Logistic regression analysis showed that the p-values of both JUN and FOSB as MetS-affecting factors were <0.05. Altogether, the findings of this study indicate that both JUN and FOSB, abnormally expressed in individuals with obesity, are good biomarkers of MetS.